The Influence of Leadership Style on the Performance of State Vocational High School Teachers in Sumenep Regency with Organizational Commitment as a Mediating Variable - Alvin Arifin; Ernani Hadiyati (Manajemen Bisnis, 2023)
This research investigates the relationship between leadership style and performance in public vocational high schools in the Sumenep Regency, with organizational commitment serving as a moderating variable. The object of this research is educators who teach at vocational high schools in Sumenep Regency. The function of the teaching profession is to disseminate information for the purpose of educating the population of a country or other entity. This research is quantitative and investigates the influence that varying factors have on one another. The data source used is primary data, and data gathering techniques use questionnaires delivered to respondents. The population of this study consisted of 211 instructors working at State Vocational High Schools (SMK) in the Sumenep Regency. 138 participants filled out the questionnaire using the Slovin method. The following are the findings that led to these conclusions from this research: (1) Leadership style has a significant effect on performance; (2) leadership style has a significant effect on organizational commitment; (3) organizational commitment has a significant effect on performance; and (4) organizational commitment significantly mediates the influence that leadership style behavior has on performance. In order to develop great students and increase student interest in attending private schools, private schools must further enhance the effectiveness of their teachers.